On the taxonomy of Anaceratagallia Zachvatkin, 1946 (Homoptera: Auchenorrhyncha: Cicadellidae: Agalliinae) of Western Kyrgyzstan - Tishechkin, Dmitri Yu. (Zootaxa, 2017)
In Western Kyrgyzstan the genus Anaceratagallia includes four species: A. venosa (de Fourcroy, 1785), A. aciculata (Horvath, 1894), A. laevis (Ribaut, 1935) = A. acuteangulata Dubovskiy, 1966 nec Zachvatkin, 1946, and A. alabugensis Dubovskiy, 1966 = A. collicola Dubovskiy, 1966, syn. n. = A. turanica Dubovskiy, 1966, syn. n. = A. laevis Dubovskiy, 1966 nec Ribaut, 1935. Illustrated descriptions and male calling signal oscillograms for all species are given. The range of A. acuteangulata Zachvatkin, 1946 includes Italy, Greece, Turkey, and North Caucasus; records of this species from Ukraine, Kazakhstan and Central Asia are erroneous. Investigation of morphological and acoustic characters in Anaceratagallia showed that small differences in the shape of male genitalia and 2nd abdominal apodemes are not species-specific traits.